Research Experiences for Students: Interdisciplinary skill development to prepare the future workforce for success. Issue 1762 (20th February 2015) - Ferrari, Nicole; Jenkins, Carol; Garofano, Jacquelynn; Day, Deborah; Schwendemann, Todd; Broadbridge, Christine
ABSTRACT: Research Experiences for Undergraduates (REU) programs traditionally function as a recruitment vehicle to encourage students to pursue further studies in STEM (Science, Technology, Engineering and Math) and as an opportunity for STEM majors to delve deeper into their chosen fields of study. Based on a critical examination of REU student feedback, evaluators at CRISP (Center for Research on Interface Structures and Phenomena) have found that in addition to these conventional benefits of research-based experiences, the value of interdisciplinary skill development is integral to the REU experience and these contributions may warrant a more formal evaluative definition. Using the emerging 21 st Century Skills Framework, CRISP has begun conducting a series of small-scale studies in an effort to define the contribution of student research experiences in cross-disciplinary skill development and the positive effects that exposure to real-world science practices have on refinement of career decisions and vocational success. Using Likert-type survey methods, this study directly examines current and former REU students' perceptions of the importance of interdisciplinary 21 st century skills such as creativity, collaboration, communication, information literacy, and problem-solving in their REU experience and their perceived value of these skills in their future and/or current careers. Through better understanding the role these "soft skills" play in student research experiences, CRISP hopes to maximize these interdisciplinary benefits within its REU program to best prepare students for the complex demands of the 21 st century workplace.